Metagenomic Insights Into the Structure and Function of Intestinal Microbiota of the Hadal Amphipods - Chan, Jiulin; Geng, Daoqiang; Pan, Binbin; Zhang, Qiming; Xu, Qianghua (Frontiers in Microbiology, 2021)
Hadal trenches are the deepest known areas of the ocean. Amphipods are considered to be the dominant scavengers in the hadal food webs. The studies on the structure and function of the hadal intestinal microbiotas are largely lacking. Here the intestinal microbiotas of three hadal amphipods, Hirondellea gigas, Scopelocheirus schellenbergi and Alicella gigantean, from Mariana Trench, Marceau Trench and New Britain Trench, respectively, were investigated. Taxonomic analysis identified 358 microbial genera commonly shared within the three amphipods. Different amphipod species possessed their own characteristic dominant microbial component, Psychromonas in H. gigas, Candidatus Hepatoplasma in A. gigantea and S. schellenbergi. Functional composition analysis showed that “Carbohydrate Metabolism”, “Lipid Metabolism”, “Cell Motility”, “Replication and Repair”, and “Membrane Transport” were among the most represented GO Categories in the gut microbiotas. To test the possible functions of “Bacterial Chemotaxis” within “Cell Motility” category, the MCP (methyl-accepting chemotaxis protein) gene involved in “Bacterial Chemotaxis” pathway was obtained and used for swarming motility assays. Results showed that bacteria transformed with the gut bacterial MCP gene showed significantly faster growths compared with the control group, suggesting MCP promoted the bacterial swimming capability and nutrient utilization ability. This result suggested that hadal gut microbes could promote their survival in poor nutrient conditions by enhancing chemotaxis and motility. In addition, large quantities of probiotic genera were detected in the hadal amphipod gut microbiotas, which indicated that those probiotics would be possible contributors for promoting host’s growth and development, which could facilitate adaptation of hadal amphipods to the extreme environment.